2010
DOI: 10.1523/jneurosci.0657-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inflammatory Pain by Activating B-Type Natriuretic Peptide Signal Pathway in Nociceptive Sensory Neurons

Abstract: B-type natriuretic peptide (BNP) has been known to be secreted from cardiac myocytes and activate its receptor, natriuretic peptide receptor-A (NPR-A), to reduce ventricular fibrosis. However, the function of BNP/NPR-A pathway in the somatic sensory system has been unknown. In the present study, we report a novel function of BNP in pain modulation. Using microarray and immunoblot analyses, we found that BNP and NPR-A were expressed in the dorsal root ganglion (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
91
4
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 58 publications
9
91
4
1
Order By: Relevance
“…The thermal sensitivity of C2 correlates with the presence of Trpv1 and Trpv2 in the Nppb gene network and the role of NBP in thermal hyperalgesia [19,45]. Both C4 and C5 are MHNs (IS).…”
Section: Functional Annotations Of Neuron Types and Related Gene-netwmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal sensitivity of C2 correlates with the presence of Trpv1 and Trpv2 in the Nppb gene network and the role of NBP in thermal hyperalgesia [19,45]. Both C4 and C5 are MHNs (IS).…”
Section: Functional Annotations Of Neuron Types and Related Gene-netwmentioning
confidence: 99%
“…Gene expression profiles of DRG tissue have been also analyzed by microarray and RNA-sequencing (RNA-seq) techniques [17,18]. Although these methods have helped to identify the expression of neuromodulators such as natriuretic peptide B (NPB) [19] and regulators of Na + , K + -ATPase (NKA), including the γ-subunit of NKA (FXYD domain-containing ion transport regulator 2, Fxyd2) [20][21][22], they cannot provide a global view of the transcriptional profiles of individual neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2010) have shown that 90% of the small IB4-positive DRG neurons from the skin have K Ca currents and RT-PCR of mRNA from these neurons shows the expression of multiple splice variants. Yu et al (2015) have shown that CaMKII blockage increases sensory sensitivity and DRG neurons firing rate.…”
Section: Membrane Properties Associated With Tonic and Phasic Firing mentioning
confidence: 99%
“…Building upon a series of important results on pain inhibition, Zhang and colleagues identified B-type natriuretic peptide (BNP) and its receptor involved in pain modulation. They demonstrated that activate BNP in nociceptive neurons could inhibit the inflammatory pain [22]. Later they revealed another protein, Activin C, is also required for inflammatory pain suppression.…”
mentioning
confidence: 99%